Computation and Analysis of High Rocky Slope Safety in a Water Conservancy Project - Meng Yang; Huaizhi Su; Xiaoqun Yan (Discrete Dynamics in Nature and Society)
An integrated method, covering the actual monitoring analysis, practical geological model, and theoretical mathematical simulation model, is systematically proposed and successfully applied. Deformation characteristic of a unique high rocky slope was firstly analyzed from multiple angles and multiple layers by changeable elevations and distances. Arrangements of monitoring points were listed and monitoring equipment was designed to comprise a complete monitoring system. Present larger displacement was concluded for bottom larger displacement caused by water erosion and middle larger displacement formed by seepage. Temporal and spatial displacements rule study of multiple-points linkage effects with water factor proved this conclusion. To better excavate useful message and analyze the deep rule from the practical monitoring data, the slope geological model was conducted and rock mechanic parameters were researched. Finally, a unique three-dimensional finite element model was applied to approach the structure character using numerical simulations. The corresponding strength criterion was used to determine the safety coefficient by selecting a typical section. Subsequently, an integrated three-dimensional finite element model of the slope and dam was developed and more detailed deformation evolution mechanism was revealed. This study is expected to provide a powerful and systematic method to analyze very high, important, and dangerous slopes.